Structural & electrical characterization of Ba(0.5)S(0.5)Tio3 thin films in effect annealing temperature - Ramadhan Adnan
This final year project is about investigated an electrical, structural and microstructural properties of fabricated doped BST thin films as a function of film composition. The details of the electrical, microstructural, and compositional properties will be examined, correlated and discussed.